Risk management with CMMI, RUP and ISO in Mining Software Engineering - Romero Baylón, Alfonso (2007)
The periods of change and continuous evolution of the information technologies and communication, every time has been reduced, thus we have; today that in the matter of software or computer science programs of application; these enter state of obsolescence in an average of six months from their put into operation. In the last two years the design of new computer science applications have undergone the most important changes in the initial approach for their design, analysis and codifi cation, therefore; ever since Bohem in 1982 warned some techniques related to the software engineering today we observed that these techniques and methodologies of analysis and design of computer science applications have varied signifi cantly in relation to the initial approach. The continuous application of the norms and techniques like CMMI, RUP and ISO have done that these are perfected year to year, appearing of this way the beta versions and/or versions in general. In this article we showed that the point I criticize of the elaboration and creation of computer science applications is in the management of risks of the project of software engineering, therefore; each technique or methodology like the CMMI, RUP or ISO always have focused in their content the management of risks in projects of software engineering.